Wild banana seed Phytobezoar Rectal impaction causing intestinal obstruction - Feng, Yih Chai; Heng, Sophia Si Ling; Siti Mohd Desa Asilah (Springer India, 2015)
Wild banana (Musa acuminata subsp. microcarpa) seed phytobezoar rectal impaction in adult is a rare entity. Here, we report a 75-year-old male with dementia who presented with lower abdominal pain, per-rectal bleeding and overflow faecal incontinence. Our investigation discovered a large wild banana seed phytobezoar impacted in the rectum causing intestinal obstruction, stercoral ulcer and faecal overflow incontinence. In this article, we discuss the patient’s clinical findings, imaging and management. The culprit plant was identified and depicted. This may be the first report of its kind. Public consumption of these wild bananas should be curtailed. It is hoped that this report would increase the awareness of such condition and its identification